A review of the subgenera Arichelonus, Megachelonus and Scabrichelonus of the genus Chelonus Panzer (Braconidae: Cheloninae) with description of five new species from China - Zhou, Jin-Jin; van Achterberg, Kees; Tang, Pu (Zootaxa, 2022)
The subgenus Arichelonus Viereck, 1913 of genus Chelonus Panzer, 1806 is newly recorded from China and five new species belonging to three different subgenera are described and illustrated from China, i.e., Chelonus (Arichelonus) allokotosus sp. nov., Chelonus (Arichelonus) kenosetrus sp. nov., Chelonus (Megachelonus) irilaminatus sp. nov., Chelonus (Megachelonus) macrodontus sp. nov., and Chelonus (Scabrichelonus) nigrifemoratus sp. nov. Keys to the currently known species of the subgenera Arichelonus, Megachelonus and Scabrichelonus are provided.